Hemingway’s Language Style and Writing Techniques in The Old Man and the Sea - Yaochen Xie (English Language Teaching, 2023)
Among many great American writers, Hemingway is famous for his objective and terse prose style. As all the novels Hemingway published in his life, The Old Man and the Sea typically reflects his unique writing style. The language is simple and natural on the surface, but actually deliberate and artificial. Hemingway’s style is related to his experience as a journalist. The influence of his style is great all over the world. The Old Man and the Sea is full of facts, most of which comes from Hemingway own experience. In the forepart of the novel, they are used to show the quality of Santiago’s life, and are narrated simply and naturally; while in the latter part of the novel, they are used from inside Santiago’s own consciousness and form part of a whole scheme of the novel